Ефективність застосування ретарданту хлормекват-хлорид у посівах пшениці озимої з різною густотою. - Ярчук, Ігор Іванович; Yarchuk, Igor; Позняк, Василь Васильович; Poznyak, Vasiliy; Кобос, І.О.; Kobos, I. (Інститут зернових культур НААН України, 2017)
The norms of sowing of seed and the plant growth regulators played an important role in improvement of technology of production of high-quality grain of winter wheat (Triticum aestivum L.). The plant growth regulators are preparations of delay of height of plants what are the analogues of natural plant hormones. Under the action of this preparations firmness of plants to the unfavorable weather-climatic terms increases. One of the plant growth regulators is Chlormeqat-chloride that is characterized of antigibberellic properties. Наведено результати трирічних досліджень впливу норм висіву насіння та застосування ретарданту хлормекват-хлорид на ріст, розвиток рослин та врожайність пшениці озимої. сорт Співанка. Встановлено, що оптимальною для неї нормою висіву є 4,5 млн. схожих насіння/га. Обробка ретардантом позитивно впливала на зростання, розвиток та формування врожаю зерна пшениці озимої; у варіанті з оптимальною нормою висіву насіння збільшення врожаю зерна становила 0,52 т/га загалом роки проведення дослідів.Aim of researches was to set efficiency of influence of treatment of sowing of winter wheat of sort Spivanka by the plant growth regulator of Chlormeqat-chloride depending on the norm of sowing of seed on a height, development and forming of harvest at growing in the conditions of north Steppe. Norms of sowing was 3.5; 4.0; 4.5; 5.0 million seeds of ha and action of preparation Chlormeqat-chloride was studied. The plants were processed by preparation in autumn at the beginning of phase of bushing out.
Efficiency of application of plant growth regulator of Chlormeqatchloride in sowing of winter wheat with the different thickness of sowing
Keywords: пшениця озима; winter wheat; норма висіву; norm of sowing of seed; ретардант хлормекват-хлорид; a plant growth regulator of Chlormequatechloride; ріст та розвиток рослин; height and development of plants; урожайність; productivity